2022
DOI: 10.1038/s41598-022-06308-2
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning detection of nanoparticles and multiple object tracking of their dynamic evolution during in situ ETEM studies

Abstract: In situ transmission electron microscopy (TEM) studies of dynamic events produce large quantities of data especially under the form of images. In the important case of heterogeneous catalysis, environmental TEM (ETEM) under gas and temperature allows to follow a large population of supported nanoparticles (NPs) evolving under reactive conditions. Interpreting properly large image sequences gives precious information on the catalytic properties of the active phase by identifying causes for its deactivation. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 67 publications
(83 reference statements)
0
16
0
Order By: Relevance
“…The model can realize various uncertainties in the evolution of the paleoclimate cycle. The model can provide users with real-time dynamic historical data, and can effectively process the original geomorphological information, so that it can play a better role in the process of paleoclimate evolution and provide reference for people's research, thus promoting the development of the theory and technology of dynamic evolution of paleoclimate environment [10] .…”
Section: Discussionmentioning
confidence: 99%
“…The model can realize various uncertainties in the evolution of the paleoclimate cycle. The model can provide users with real-time dynamic historical data, and can effectively process the original geomorphological information, so that it can play a better role in the process of paleoclimate evolution and provide reference for people's research, thus promoting the development of the theory and technology of dynamic evolution of paleoclimate environment [10] .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, AI-enabled nanoparticle synthesis platforms and nanoparticle delivery systems (AI-assisted algorithms) have been adopted to optimize the synthesis and delivery of magnetic nanoparticles for anticancer drug delivery, respectively. It uses machine learning, deep learning, and computer vision techniques to predict the optimal parameters for nanoparticle synthesis that accurately target the nanoparticles to the desired cells [ 258 , 259 ]. Furthermore, AI-assisted algorithms have also been employed to track the magnetic nanoparticles and monitor the toxicity of the drug during delivery to provide insights into cancer progression and identify potential therapeutic strategies [ 260 ].…”
Section: Cancer Therapymentioning
confidence: 99%
“…NP trajectories and their fusion events were precisely retrieved from the experimental data set enabling the accurate determination of NP behavior. 85…”
Section: ■ Advances In In Situ and Operando Gas Cellmentioning
confidence: 99%
“…For example, in an ETEM setup, Faraz et al have reported the calcination process of Pd­(O)@δ-Al 2 O 3 nanoparticles in an oxygen environment, where DL algorithms were utilized for the quantitative analysis of the evolution of NPs under reactive conditions. NP trajectories and their fusion events were precisely retrieved from the experimental data set enabling the accurate determination of NP behavior . Further, several AI-developed programs are already commercially available and can perform in situ TEM experiments with minimal thermal drift, better synchronization between the column, detectors, and camera, and a facile transition from TEM to STEM mode.…”
Section: Summary and Prospectsmentioning
confidence: 99%